Association of sporadic and familial Barrett's esophagus with breast cancer. Issue 4 (7th March 2018) - Chan, M Q; Blum, A E; Chandar, A K; Emmons, A M L Kieber; Shindo, Y; Brock, W; Falk, G W; Canto, M I; Wang, J S; Iyer, P G; Shaheen, N J; Grady, W M; et al.
SUMMARY: Barrett's esophagus (BE) is the only known precursor to esophageal adenocarcinoma (EAC). Based on striking aggregation of breast cancer and BE/EAC within families as well as shared risk factors and molecular mechanisms of carcinogenesis, we hypothesized that BE may be associated with breast cancer. Pedigree analysis of families identified prospectively at multiple academic centers as part of the Familial Barrett's Esophagus Consortium (FBEC) was reviewed and families with aggregation of BE/EAC and breast cancer are reported. Additionally, using a matched case-control study design, we compared newly diagnosed BE cases in Caucasian females with breast cancer (cases) to Caucasian females without breast cancer (controls) who had undergone upper endoscopy (EGD). Two familial pedigrees, meeting a stringent inclusion criterion, manifested familial aggregation of BE/EAC and breast cancer in an autosomal dominant inheritance pattern with incomplete penetrance. From January 2008 to October 2016, 2812 breast cancer patient charts were identified, of which 213 were Caucasian females who underwent EGD. Six of 213 (2.82%) patients with breast cancer had pathology-confirmed BE, compared to 1 of 241 (0.41%) controls ( P -value < 0.05). Selected families with BE/EAC show segregation of breast cancer. A breast cancer diagnosis is marginally associated with BE. We postulate a common susceptibility between BE/EAC and breast cancer.